If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14m + -21 = 0 Reorder the terms: -21 + 14m = 0 Solving -21 + 14m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 14m = 0 + 21 Combine like terms: -21 + 21 = 0 0 + 14m = 0 + 21 14m = 0 + 21 Combine like terms: 0 + 21 = 21 14m = 21 Divide each side by '14'. m = 1.5 Simplifying m = 1.5
| (w-4/9)(-2/3) | | 3x-3y/2= | | S=2.5w | | 1/6x1/6x1/6x1/6= | | -4m-5= | | y=-2/3x0 | | 3x-3y/2 | | 1/6-5/9= | | -8a-12b= | | 6x-19=4(7+4x) | | -12=-5p-8+6p | | 1=20-3x | | f(x)=325-10x | | cosx/sin2x=5/7 | | 6a+12=9 | | X/2-1=2x/3-8 | | y=4x^3-7x+2 | | -12.2+x=-4.5 | | 8707.37+h=20321.5 | | 3+15t=30 | | 30*3-15=t | | X=-5y+13 | | 12=2e^5 | | 16a+24ab= | | X-5(1)=11 | | -4(2/2--4)^2=-4/9 | | 18/k=6/95 | | 8=16 | | 7/2=y/6 | | C/5-1=1 | | x-50+19=108 | | 4(x-4)=28+4c |